2019
DOI: 10.1097/md.0000000000015712
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of combined use of propofol and etomidate for sedation during gastroscopy

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 37 publications
(56 reference statements)
0
20
0
Order By: Relevance
“…Previous study has shown that the physical and chemical properties of the admixture of propofol and etomidate have not changed, it can be safely used in clinical anesthesia, and its compatibility is stable. [ 11 ] Many researches have confirmed that the admixture of propofol and etomidate not only maintains the stability of the respiratory system of patients, but also reduces the incidence of adverse reactions such as injection pain, nausea and vomiting, [ 12 ] hypoxemia, [ 13 ] hypotension and oxygen desaturation. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study has shown that the physical and chemical properties of the admixture of propofol and etomidate have not changed, it can be safely used in clinical anesthesia, and its compatibility is stable. [ 11 ] Many researches have confirmed that the admixture of propofol and etomidate not only maintains the stability of the respiratory system of patients, but also reduces the incidence of adverse reactions such as injection pain, nausea and vomiting, [ 12 ] hypoxemia, [ 13 ] hypotension and oxygen desaturation. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has shown that when etomidate is used for induction of anesthesia, the incidence of muscle spasm is as high as 50% to 80%, and it is dose-dependent. [ 12 ] Muscle spasm causes postoperative myalgia, increases blood potassium and other adverse reactions, especially increases gastrointestinal motility after muscle tremor, leading to an increased risk of vomiting and aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…If substantial heterogeneity occurred (I 2 > 50% or p < 0.05), a random effects model was used to calculate the pooled MD (Chen et al 2019). Publication/reporting biases were visually assessed using funnel plots.…”
Section: Discussionmentioning
confidence: 99%
“…A clear surgical field becomes the most basic requirement that minimally invasive surgeries must meet. 9 In hand and foot surgeries, the application of tourniquets can meet the requirements of surgeons for clarity of surgical field, but collateral injury occurs from limb I/R. 10 , 11 Earlier studies showed that I/R of the hind limbs in rats can lead to lung injury at distance sites.…”
Section: Discussionmentioning
confidence: 99%